Testing of Standardized Advertising Slogans Within the Marketing Communication of Sustainable and Local Foods in Order to Reveal Consumer Preferences - Alena Kusá (Frontiers in Sustainable Food Systems, 2021)
Marketing communication concerning the consumer in the retail food market is currently undergoing significant changes, based on a shift from the passive supply to manage the consumer, toward an effort to understand his needs. The changes in communication are influenced by the technological revolution, which has also significantly affected retail and consumer shopping behavior, resulting in the modern changes in how to approach customers nowadays. Marketing communication must respond to changes in purchasing behavior with the greatest possible flexibility and ability to follow current trends. The presented research will aim to present the importance of the topic and emphasize its topicality by defining specific forms of communication causing an increase in consumer interest in local and sustainable food. Part of the aim of the presented work will be a general proposal for applying specific forms of marketing communication, increasing the interest of consumers in local foods characterized by the attribute of sustainability. The theoretical basis of the work presents current knowledge focused on marketing communication about sustainability in the food chain and consumers' relationship to local and sustainable food, which builds the communication. The work is based on collecting primary data and their subsequent management by mathematical and statistical methods. Friedman's test as a method used for data processing allows us to reveal differences in consumer preferences between various forms of standardized marketing communication to increase local, sustainable foods to engage the consumer. Independently of the Friedman test, the Chi-square test allows us to find races among the individuals corresponding to the respondents. The research results reveal that the differences between the various forms of standardized marketing communication bring a new perspective on the role of communication with the consumer. The results also reveal the role of a specific label expressing the sustainability of local foods. The benefit of our work is to set recommendations for producers and distributors of local and sustainable foods in the field of marketing communication.